In Vivo Modulation of Rat Liver Microsomal Cytochrome P450 Activity by Antimalarial, Anti-HIV, and Antituberculosis Plant Medicines - Regina Appiah-Opong PhD; Isaac Tuffour MPhil; Ebenezer Ofori-Attah BSc; Abigail Aning BSc; Philip Atchoglo BSc; Eunice Ampem Danso MPhil; Believe Ahedor MPhil; Samuel Adjei PhD; Alexander K. Nyarko PhD (SAGE Publishing, 2018)
Drug interactions are key reasons for adverse drug reactions and attrition from market. Major infectious diseases causing morbidity/mortality in Ghana are malaria, tuberculosis, and HIV/AIDS. In this study, plant medicines commonly used to treat/manage these diseases in Ghana were investigated for their potential to modulate rat cytochrome P450 enzyme activities. Fluorescence and high-performance liquid chromatography-based assays were used to assess effects of antimalarial plant medicines, Fever (FEV), Mal-TF (MAL), and Kantinka terric (KT); anti-TB medicines, Chestico (CHES), CA + ST Pains + HWNT (TF), and Kantinka herbatic (KHB); and anti-HIV/AIDS medicines, Wabco (WAB), AD + T/AD (LIV) and Kantinka BA (KBA) on rat liver microsomal cytochrome P450 enzyme activities. Effects of medicines on rat biochemical and hematological parameters were also assessed. Generally, the medicines altered microsomal CYP1A1/1A2, CYP2B1/2B2, CYP2C9, and CYP2D6 activities. Only KBA elicited an increase (80%) in CYP1A1/1A2 activity. FEV, MAL, CHES, WAB, and LIV strongly inhibited the enzyme activity. All the medicines significantly inhibited CYP2C9 (24%-80%) activity. CYP2D6 activity increased after treatment with MAL, KBA, LIV, and TF. Also, MAL, WAB, LIV, KHB, and CHES increased CYP2B1/2B2 activity, while KT decrease the activity. Generally, the medicines altered liver function in the rats. Cholesterol levels declined after KBA treatment only. White and red blood cell counts, hemoglobin and hematocrit levels were significantly reduced in KT- and KBA-treated rats. Our results suggest that use of the medicines could have implications for drug interactions and safety, particularly if the medicines are administered over prolonged periods. Further investigations are imperative to establish clinical relevance of these results.